Collimation scheme for fiber lens using polymer coating - Jaemyoung Lee (2012 8th International Conference on Computing and Convergence Technology, 2012)
We propose a new fiber lens scheme to extend the working distance by applying a polymer layer to the fiber lens. The numerical analysis shows that the working distance can be extended to larger than 10 times the working distance of a fiber lens without the layer.